Grace Stamps: capstone - Stamps, Grace, artist (Colorado State University. Libraries, 2015)
The artist's statement: As a multiracial woman I find it difficult to relate to any singular culture. Though I participate within both white and black American communities, my personal involvement has often been contradictory or inharmonious. I am neither "black-enough" nor "white-enough." I am unable to fully connect with, or emulate, key characteristics of either black or white culture. Thus, I have always felt suspended between the two, belonging to neither. I have turned to painting to explore-and in effect create-my own cultural and racial identity. By taking popular visual media that deals with black or white American culture, I dismantle the imagery through formal conventions (line, color, composition, etc.) to literally deconstruct my identity. The vibrant colors in my paintings reflect the energetic behaviors, beliefs, and actions of the cultural group in question while I am presented as a grey figure. My hue in my paintings-or lack thereof-is a visual representation of identifying as black and white (black + white = grey) and falling between two cultures in a "grey zone." In addition, the lack of vibrancy in my skin further emphasizes my inability to assimilate with, or reflect, the vibrant cultures surrounding me. At times my "assimilation" may appear forced or voluntary; violent or passive; recognizable or foreign. I find catharsis in using paint to explore my conceptions of self. I have always struggled with my racial and cultural identity. By taking control-creating my own culture through fine art-I am able to explore what it means to me to be biracial and construct a personal, cultural space to exist within.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: painting